Synthesis, Spectral Characterization and Biological Activity of Dithiocarbamate-based Ligand and its Metal Complexes - Mohamad J. Al-Jeboori (Journal of Global Pharma Technology, 2018)
This work is based on the synthesis, structural characterization and biological activity of somedithiocarbamate-based complexes. The free dithiocarbamate ligand was prepared via several synthetic routesincluding the formation of Schiff-base. The reaction of 2,6-diaminopyridine with benzaldehyde resulted in theformation of Schiff-base which reduced to the corresponding diamine by methanolic NaBH 4 . The reaction ofdiamine with CS 2 in a methanolic solution of KOH resulted in the preparation of the free dithiocarbamateligand. Macrocyclic complexes were formed from the reaction of the appropriate metal chloride with the ligandin an ethanolic medium. The suggested geometries around metal centres were determined using a range ofphysicochemical and spectroscopic techniques. The analytical and spectroscopic data revealed the formationof four and six coordinate complexes. Complexes of the general formula [M(L)] 2 (where M= Fe(II), Co(II) andZn(II) indicated metal centres adopt tetrahedral geometries. Complexes with the general formula [M(L)(H 2 O) 2 ] 2(where M= Mn(II), Ni(II), Cu(II) indicated octahedral structures around metal centres. Biological activity of theligand and its complexes against four strains of bacteria (Escherichia coli (E. coli), Pseudomonas aeruginosa,Bacillus cereus and Staphylococcus aureus) and antifungal activity against two types of pathogenic fungi,Aspergillus niger and Aspergillus parasiticus are tested.Keywords: Dithiocarbamate ligand; Transition metal complexes; Spectral characterization; Biological activity.